A defense of abortion - Boonin, David (Cambridge University, 2013)
David Boonin has written the most thorough and detailed case for the moral permissibility of abortion yet published. Critically examining a wide range of arguments that attempt to prove that every human fetus has a right to life, he shows that each of these arguments fails on its own terms. He then explains how even if the fetus does have a right to life, abortion can still be shown to be morally permissible on the critic of abortion's own terms. Finally, he considers several arguments against abortion that do not depend on the claim that the fetus has a right in life - arguments based on the golden rule, on principles of uncertainty or on various feminist theories - and concludes that these, too, are ultimately unsuccessful." "This major book will be especially helpful to those teaching applied ethics and bioethics whether in philosophy departments or professional schools of law and medicine. It will also interest students of women's studies as well as all general readers for whom abortion remains a high-profile and complex issue.